Chemopreventive role of proteins and polysaccharides from Pleurotus tuber-regium - Abdullah, Erlina; Amirullah, Nur Amalina; Vijayan, Hemapriyaa; Abd Rashid, Norhashima; Abdullah, Noorlidah; Zainal Abidin, Nurhayati (Elsevier, 2024)
Cancer ranks as the second largest cause of death worldwide. Tremendous work has been done in cancer research and development, yet the incidence of cancer still rises each year. Cancer cells are becoming more resistant to anti-cancer drugs leading to cells desensitization, while other therapies such as chemotherapy, surgery, radiotherapy, and immunotherapy are associated with toxicities and adverse effects that contribute to the increasing numbers of mortality. The best and ideal treatment is a novel medication that can select and destroy only cancer cells, thus preventing carcinogenesis without destroying the normal cells. Numerous studies have proven the potency of cytotoxic proteins and polysaccharides isolated from mushrooms against different types of cancer cell lines. Most of the polysaccharides and polysaccharide-derived compounds did not exert direct cytotoxic effects against tumor cell lines but they were utilizing the immune system via activation of cellular components, and increasing the macrophages' functional activity, thus improving the body's systems and defenses against cancers. Cytotoxic proteins are reported to be of potential significance as experimental tools in cell biology, especially tumor cell physiology, and as anti-tumor agents or toxic components of anti-tumor immunotoxins. Pleurotus tuber-regium has been consumed as a traditional remedy for the treatment of various ailments in different countries such as Nigeria, India, Africa, and Malaysia. Numerous studies have reported the significant potential cytotoxic proteins extracted from P. tuber-regium candidates against the proliferation of different cancer cell lines. Our previous study has shown a remarkable cytotoxic effect of proteins isolated from P. tuber-regium against breast cancer cell lines (MDA-MB-231), with IC50 values < 20 μg/ml. Further study has successfully characterized several proteins from the P. tuber-regium and two were identified as kinesin-like proteins and keratin type 1, cytoskeletal 10, which are suspected responsible for the cytotoxic effects towards the MDA-MB-231 cells. The kinesin-like proteins could act as inhibitors for kinesin overexpression in tumor cells which eventually lead to mitotic defect and mitotic arrest of certain tumor cells. On the other hand, keratins play a role in cell invasion and metastasis by acting as multifunctional regulators of epithelial tumorigenesis.